Clima organizacional y su incidencia en el desempeño laboral: caso Gobierno Autónomo Descentralizado del cantón de Pujilí - Jácome León, María Augusta (2017)
The organizational climate in the public institutions like the Autonomous Decentralized Government of Pujilí canton, it has taken a great importance, because it seeks to determine if there is an incidence of this in the labor performance of each one of those who make up this institution, being that it is closely linked with the motivational factors in their work environment. The objective of the research is to determine if there is an incidence between the organizational climate and the work performance of the employees, for which they were analyzed some dimensions such as; internal communication, recognition, interpersonal relationships at work, decision making, commitment, adaptation to change and the physical environment that are fundamental pillars for the institutions that provide services. The research method to be applied will be from the non-exploratory quantitative research approach, descriptive cross-sectional that was used in the survey technique and whose instrument was the measurement of the organizational weather of the authors Chiang, Núñez and Salazar; In addition, we worked with the evaluation of work performance with indicators that measure their performance in the work, this one was qualified by the director of human talent where the collected data were tabulated in the SPSS statistical software. The target population was 78 public servants of indefinite contract. The result obtained from this study is a Pearson correlation coefficient r of -0.053 which is considered as a null relation, this means that the variables of organizational weather and work performance don´t related of directly and indirectly manner. The research generated in the pujili GAD a technical impact from this will have an instrument that allows you to take into consideration the organizational climate and a social impact that it can be visualized between users and servers. The research generated in the Pujilí GAD a technical impact from the present will have an instrument that allows it to take into consideration the organizational climate and a social impact that can be visualized between servers and users.